PENGARUH KEBIJAKAN PAJAK EKSPOR TERHADAP KETERSEDIAAN MINYAK SAWIT MENTAH (CPO) DI DALAM NEGERI : Pendekatan Produsen dan Konsumen Surplus - Abd. Rauf, Rustam (FAPETKAN UNTAD, 2005)
The purpose of this research is to understand the concept macroeconomic policy effectiveness, fiscal policy in particular using the rate of crude palm oil (CPO) tax in Indonesia. The method used is classical welfare analysis (CWA) through market demand and supply analysis approach. The results using the rate of crude palm oil (CPO) tax and the exchange rate of US dollar showed that an inreasing in the CPO tax will decrease in surpluss consumers loss. On the other hand, a change in export tax will reduce the pruduser surpluss, while the goverment revenue will increase in line with an increase in export tax between 5% to 15%. Never the less an icreasing in the CPO tax at from 5% to 15% will reduce a net social welfare. Key words : Policy, CPO, consumers surpluss, Producer surpluss.